Revitalisasi Sungai sebagai Upaya Peningkatan Kesejahteraan Sosial dan Ekonomi di Desa Lebak Jabung Mojokerto - Fikriyahtus Salehah, Jihan; Falasifah, Nihlatul (CV Omah Kreator, 2024)
Rivers are living lands that play a very important role in the lives of community members. Not only is it a source of water for daily use and agriculture, but it is also a source of recreation that supports the local village economy. This article discusses river revitalization efforts as a way to improve the quality of the Moro River, the river will be discussed on a scale to make it better than before. In the village of Lebak Jabung, in Jatirejo subdistrict, Mojokerto district, the Moro river is located. This river has the potential for an excellent tourist destination and should be protected. However, environmental pollution and changes in land use threaten its beauty. The asset based community development approach is proposed through research on river revitalization as a strategy for improving environmental, economic and social quality. We show river tubing facilities in the text, so the research results show that river revitalization can increase the number of visitors and the village economy. The river is degraded again. which means that vitality has potential vulnerabilities. Researchers concluded that the results of the research obtained were regarding improving water quality, such as increasing water quality parameters and increasing public knowledge regarding the importance of maintaining river ecosystems